Binaural interference with simulated electric acoustic stimulation - van Ginkel, Chantal (J Acoust Soc Am, 2019)
Preserved low-frequency acoustic hearing in cochlear implant (CI) recipients affords combined electric-acoustic stimulation (EAS) that could improve access to low-frequency acoustic binaural cues and enhance spatial hearing. Such benefits, however, could be undermined by interactions between electrical and acoustical inputs to adjacent (spectral overlap) or distant (binaural interference) cochlear places in EAS. This study simulated EAS in normal-hearing listeners, measuring interaural time difference (ITD) and interaural level difference (ILD) discrimination thresholds for a low-frequency noise (simulated acoustic target) in the presence or absence of a pulsatile high-frequency complex presented monotically or diotically (simulated unilateral or bilateral electric distractor). Unilateral distractors impaired thresholds for both cue types, suggesting influences of both binaural interference (which appeared more consistently for ITD than ILD) and physical spectral overlap (for both cue types). Reducing spectral overlap with an EAS gap between 1 and 3 kHz consistently improved binaural sensitivity. Finally, listeners displayed significantly lower thresholds with simulated bilateral versus unilateral electric stimulation. The combined effects revealed similar or better thresholds in bilateral full spectral overlap than in unilateral EAS gap conditions, suggesting that bilateral implantation with bilateral acoustic hearing preservation could allow for higher tolerance of spectral overlap in CI users and improved binaural sensitivity over unilateral EAS.